Control strategy for carbapenemase-producing Enterobacteriaceae in nursing homes: perspectives inspired from three outbreaks. Issue 2 (February 2019) - Legeay, C.; Hue, R.; Berton, C.; Cormier, H.; Chenouard, R.; Corvec, S.; Birgand, G.
Summary: Three outbreaks of carbapenemase-producing Enterobacteriaceae (CPE) in three nursing homes in western France were retrospectively assessed. In all, ten cases of colonization or infection with CPE were detected upon admission in neighbouring hospitals. Antibiotic consumption or high frailty was infrequent among them. Nursing homes should be included in a regional strategy to limit CPE spread.